Advances in molecular‐replacement procedures: the REVAN pipeline. (1st September 2015) - Carrozzini, Benedetta; Cascarano, Giovanni Luca; Giacovazzo, Carmelo; Mazzone, Annamaria
<x xml:space="preserve">Abstract</x> The REVAN pipeline aiming at the solution of protein structures via molecular replacement (MR) has been assembled. It is the successor to REVA, a pipeline that is particularly efficient when the sequence identity (SI) between the target and the model is greater than 0.30. The REVAN and REVA procedures coincide when the SI is >0.30, but differ substantially in worse conditions. To treat these cases, REVAN combines a variety of programs and algorithms (REMO09, REFMAC, DM, DSR, VLD, free lunch, Coot, Buccaneer and phenix.autobuild). The MR model, suitably rotated and positioned, is first refined by a standard REFMAC refinement procedure, and the corresponding electron density is then submitted to cycles of DM–VLD–REFMAC. The next REFMAC applications exploit the better electron densities obtained at the end of the VLD–EDM sections (a procedure called vector refinement). In order to make the model more similar to the target, the model is submitted to mutations, in which Coot plays a basic role, and it is then cyclically resubmitted to REFMAC–EDM–VLD cycles. The phases thus obtained are submitted to free lunch and allow most of the test structures studied by DiMaio et al. [(2011), Nature (London), 473, 540–543] to be solved without using energy‐guided programs.